Diversity of electronic educational games concept - Santos Filho, José Walter; Nou Schneider, Henrique (Revista Colombiana de Computación, 2011)
The aim of this paper is to report the state of the art on the concept of Educational Electronic Game, in view of the diversity of existing conceptions about the use of games in Education. To achieve this we investigated the scientific literature of the late twentieth century and the first ten years of the century on the subject, noting that the ownership of the video game from the education you intend to use games developed with recreational function and apply them in ways tailored to reach educational goals. This opportunity offers space to be used in teaching games that were developed by observing conditions psycho-pedagogical selection and adoption of strategies of teaching, breadth of content to be treated, modeling behavior of User, and other aspects of the video game education.